The European Commission and the Establishment of the European Neighbourhood Policy: A Case-Study for Institutionalist Analysis? (Polish Yearbook of International Law, 2024)
Despite the mushrooming literature on the European Neighbourhood Policy (ENP) and its numerous problems, little attention has been given to the analysis of its origins. Upon examining the scholarship, two contending explanations emerge regarding the policy’s formulation stage. While one perspective maintains that the policy was influenced by the European Commission’s past experience, the other highlights how the policy was affected by the European Commission’s desire to expand its powers vis-à-vis other European Union (EU) actors. Against this backdrop, this paper first seeks to frame both perspectives in theoretical terms. Then, through process-tracing analysis and elite interviews, it aims to determine which theoretical model not only better explains the structure of the Neighbourhood Policy, but also evaluates the nature of the interaction between European Union Member States and the European Commission throughout the policy’s formulation stage. In doing so, the paper seeks to expand our knowledge of the ENP’s genesis, as well as highlight the efficacy of institutionalist analysis of the European Neighbourhood Policy.